2003
DOI: 10.3327/jnst.40.370
|View full text |Cite
|
Sign up to set email alerts
|

Background-Cross-Section-Dependent Subgroup Parameters

Abstract: A new set of subgroup parameters was derived that can reproduce the self-shielded cross section against a wide range of background cross sections. The subgroup parameters are expressed with a rational equation which numerator and denominator are expressed as the expansion series of background cross section, so that the background cross section dependence is exactly taken into account in the parameters. The advantage of the new subgroup parameters is that they can reproduce the self-shielded effect not only by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…(8) and (9) It may be worth noting that the 'plus terms' h t n i uþ appear only at relatively high order of power series in Eq. (8): this result is understood more easily if Eqs. (5) are multiplied by 0 N in advance and shown that the 'plus terms' are existent only in high order terms in the both equations.…”
Section: A General Comparison Of Fitting Methods and The Moment Mementioning
confidence: 86%
See 2 more Smart Citations
“…(8) and (9) It may be worth noting that the 'plus terms' h t n i uþ appear only at relatively high order of power series in Eq. (8): this result is understood more easily if Eqs. (5) are multiplied by 0 N in advance and shown that the 'plus terms' are existent only in high order terms in the both equations.…”
Section: A General Comparison Of Fitting Methods and The Moment Mementioning
confidence: 86%
“…(8) and (9) does not directly appear in the actual derivation of the parameters in the fitting and the moment method. Let us look into the derivation scheme of the two methods.…”
Section: More Detailed Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…This equation is originally proposed for sub-group parameter generation [11], but s b dependency for the usual multi-group cross-section is larger than that for the sub-group cross-section. In order to improve the interpolation accuracy of s g , the polynomial hyperbolic tangent formulation is derived in the present study as a natural extension of Equation (11):…”
Section: New Derivation Of Polynomial Hyperbolic Tangent Format Librarymentioning
confidence: 99%
“…In the previous paper, the author derived a general formula that define the subgroup parameters including the background-cross-section dependence of the parameters. 8) The direct application of the formula can produce the 'best' definition of the subgroup parameters for a given set of subgroup boundaries, i.e., the lower and upper boundaries of the total cross sections of each subgroup. At the same time, the equation is general in the sense that it is extendable to the both subgroup methods.…”
Section: Introductionmentioning
confidence: 99%